Growth, cellulose, and lignin content of ramie (Boehmeria nivea L. Gaudich) with treatment of Gibberelic Acid (GA3) - WIDYA MUDYANTINI (Society for Indonesian Biodiversity, 2008)
The aims of this research were to: (i) study the effects of gibberellic acid (GA3) to the growth of Boehmeria nivea L. Gaudich, and (ii) study the effects of gibberellic acid (GA3) to the cellulose and lignin content of B. nivea. GA3 could delivered starch hydrolysis that could support Î±-amylase formation that would increase glucose. Increasing glucose concentration caused the rising of osmotic pressure inside the cell so that the cells expand. The initial synthetic path of cellulose was glucose, as well as lignin. If GA3 could increased the glucose amount inplant, then the cellulose and lignin amount also increased. This experiment use Completely Random Design with one factor, they are concentration gibberellic acid that consist of 6 treatment concentration are GA3 0 ppm, GA3 50 ppm, GA3 100 ppm, GA3 150 ppm, GA3 200 ppm, and GA3 250 ppm. The treatment to the rhizome had been done before it was planted. Some parameters like growth and anatomy parameter are measured. The results showed that treatment GA3 affect to the improvement of bud stem diameter, length of bud stem, thewet weight, dry weight, length of phloem bundle, phloem number, and lignin content but they does not affect to the change of bud number, leaf number, and cellulose content. The treatment of GA3 on GA3 200 ppm show the maximum result to the improvement of bud stem diameter, length of bud stem, the wet weight, dry weight, length of phloem bundle, phloem number, and cellulose content The treatment of GA3 on GA3 250 ppm show maximum result to the improvement of bud number, leaf number, and lignin content.Key words: gibberellic acid, Boehmeria nivea L. Gaudich, growth, cellulose content, lignin content.